'gamma': An R Package for Dose Rate Estimation from In-Situ Gamma-Ray Spectrometry Measurements - Lebrun, Brice; Frerebeau, Nicolas; Paradol, Guilhem; Guérin, Guillaume; Mercier, Norbert; Tribolo, Chantal; Lahaye, Christelle; Rizza, Magali (Ancient TL, 2020)
In situ gamma spectrometry is a useful technique used by the Luminescence and ESR dating community to improve the representativity of dose rate measurements in the context of gamma dose rate heterogeneities around dated material. This paper presents `gamma', a new R package and its graphical user interface `gammaShiny', allowing a reliable and reproducible workflow for in situ gamma spectrometry data analysis in the context of luminescence and ESR dating.